2020
DOI: 10.13189/cea.2020.080104
|View full text |Cite
|
Sign up to set email alerts
|

Elderly Perception of Critical Issues of Pedestrian Paths

Abstract: Pedestrians aged over 65 are known to be a critical group in terms of road safety because they represent the age group with the highest number of fatalities or injured persons in road accidents. It is therefore important to identify and characterize how old pedestrians perceive pedestrian paths with respect to their age related declines in perceptual and physical abilities and with respect to their experiences as road users. The aim of this study is first of all to understand which critical issues old pedestri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…However, other methods such as fuzzy fault tree analysis, TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution), AHP (Analytic Hierarchy Process), and cluster analysis could be useful to address this topic and could be used in the future to further analyze the problem. Other studies in the literature used these methods in transportation fields [30][31][32][33][34]. Despite being based on a small sample of roundabouts, this study contributes to increasing knowledge about unsafe driving behaviors at double-lane roundabouts.…”
Section: Discussionmentioning
confidence: 96%
“…However, other methods such as fuzzy fault tree analysis, TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution), AHP (Analytic Hierarchy Process), and cluster analysis could be useful to address this topic and could be used in the future to further analyze the problem. Other studies in the literature used these methods in transportation fields [30][31][32][33][34]. Despite being based on a small sample of roundabouts, this study contributes to increasing knowledge about unsafe driving behaviors at double-lane roundabouts.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, this issue was more distinct in the case of older pedestrians. This study also highlighted that pedestrian crossings with uneven surfaces or poor markings discouraged walking among senior pedestrians as it added to their inherent problems of pedestrian-vehicle conflict [70,71]. The seniors usually have a slower gait speed [72], and they reported that the pedestrian crossing time at traffic signals must be adequate for them to cross the road.…”
Section: Discussionmentioning
confidence: 88%
“…Other researchers analyzed samples of people 65 years old and older (Table 1). Still others selected an age range starting at 50 years (Hamido, Hamamoto et al, 2021), 55 or 70years old (Nishiuchi, Park et al, 2021;Pulvirenti, Distefano et al, 2020). Although most scholars adopt 65 years as the standard to define the elderly, there is no uniformity and no comparison of differences between different samples.…”
Section: Definition Of the Elderlymentioning
confidence: 99%
“…Many researchers have investigated the influencing factors of crashes in the elderly (Al AlKheder, AlRukaibi et al, 2020;Amiri, Sadri et al, 2020;Casado-Sanz, Guirao et al, 2019;Haule, Sando et al, 2019;Noh, Kim et al, 2018;Pan, Wu et al, 2022;Park, Choi et al, 2021;Wen, Qu et al, 2021;Yuan, Q., Zhang et al, 2022;, the spatial and temporal distribution characteristics of the elderlyinvolved accidents (Cardona, Arango et al, 2017;Chang, Li et al, 2020;Etehad, Yousefzadeh-Chabok et al, 2015;Freitas, Bonolo et al, 2015;Kang, Cho et al, 2018;Nishino, 2013;Prochowski, Gidlewski et al, 2018;Sadeghi-Bazargani, Samadirad et al, 2018;Sagar, Stamatiadis et al, 2020;Setiawan, 2021), safety awareness and risk cognition of the elderly (Doi, Ishii et al, 2020;Guo, Shi et al, 2018;Hamido, Hamamoto et al, 2021;Handa and Mitobe, 2020;Jian and Shi, 2020;Laosee, Rattanapan et al, 2018;Makizako, Shimada et al, 2018;Nakagawa, 2019;Nishiuchi, Park et al, 2021;Pulvirenti, Distefano et al, 2020;Söllner and Florack, 2019;Uchibori, Handa et al, 2021). Using traditional traffic safety analysis methods, scholars have analysed the relationship between the number or severity of crashes and various factors involving human error, vehicles and the road environment to find the cause of accidents.…”
Section: Introductionmentioning
confidence: 99%